A survey of fermentation products and bacterial communities in corn silage produced in a bunker silo in China. (3rd May 2013) - Wang, Chao; Han, Hongyan; Gu, Xueying; Yu, Zhu; Nishino, Naoki
Abstract To evaluate the current practice of corn silage management in China, samples of bunker‐made silage were collected from 14 farms within a 500‐km radius of Beijing for the analysis of fermentation products and bacterial communities. Mean values for dry matter (DM) content were as low as 250 g/kg in both corn stover (St) and whole crop corn (Wc) silages, and pH values averaged 4.48 and 3.73, respectively. Only three of the 14 silages exhibited a lactic‐to‐acetic acid ratio > 1.0, indicating that the presence of acetic acid was predominant in fermentation. Although 1, 2‐propanediol content was marginal in most cases (< 5.0 g/kg dry matter (DM)), two Wc silages had 1, 2‐propanediol levels > 25 g/kg DM. In contrast, 3 St silages had large amounts (> 10 g/kg DM) of butyric acid, and two of the three butyrate silages also had high concentrations of 1‐propanol. Denaturing gradient gel electrophoresis analysis demonstrated that the bacterial community appeared similar in 10 out of the 14 silage samples. Bands indicating Lactobacillus buchneri, L. acetotolerans and Acetobacter pasteurianus were found in both the St and Wc silages, accounting for the high acetic acid content found across silage samples.